A Phase I/II Study Of The Safety And Pharmacokinetics Of Nevirapine In HIV-1-Infected Pregnant Ugandan Women And Their Neonates (HIVNET 006) - Musoke, Philippa; Guay, Laura A.; Bagenda, Danstan; Mirochnick, Mark; Nakabiito, Clemensia; Fleming, Thomas; Elliott, Terry; Horton, Scott; Dransfield, Kevin; Pav, Joseph W.; Murarka, Amal; Allen, Melissa; et al. (Aids, 1999)
To determine the safety, pharmacokinetics, tolerance, antiretroviral activity, and infant HIV infection status after giving a single dose of nevirapine to HIV-1-infected pregnant women during labor and their newborns during the first week of life.An open label phase I/II study.Tertiary care hospital, Kampala, Uganda.Nevirapine, 200mg, was given as a single dose during labor to 21 HIV-1-infected pregnant Ugandan women. In cohort 1, eight infants did not receive nevirapine whereas in cohort 2, 13 infants received a single dose of nevirapine, 2mg/kg, at 72h of age.The number and type of adverse events; nevirapine concentrations in the plasma and breast milk; maternal plasma HIV-1 RNA copy number before and up to 6 weeks after delivery; and HIV-1 infection status of the infants were monitored.Nevirapine was well tolerated by women and infants; no serious adverse events that were related to nevirapine were observed. Median nevirapine concentration in the women at delivery was 1623ng/ml (range 238-2356ng/ml); median cord/maternal blood ratio of 0.75 (0.37-0.93). The median half-life in women was 61.3h (27-90h) and the transplacental nevirapine half-life in infants who did not receive a neonatal dose was 54h. The median half-life after a single dose at 72h in infants was 46.5h. During the first week of life, the median colostrum/breast milk to maternal plasma nevirapine concentration was 60.5% (25-122%). The median nevirapine concentration in breast milk 1 week after delivery was 103ng/ml (25-309ng/ml). Plasma nevirapine concentrations were above 100ng/ml in all infants from both cohorts tested at age 7 days. Maternal HIV-1 RNA levels decreased by a median of 1.3 logs at 1 week postpartum, and returned to baseline by 6 weeks postpartum. Detectable plasma HIV-1 RNA was observed in one out of 22 (4.5%) infants at birth; three out of 21 (14%) at 6 weeks; and four out of 21 (19%) at 6 months of age.The administration of a single dose of nevirapine to women during labor and to their newborns at 72h was well tolerated and showed potent antiretroviral activity in the women at 1 week after dosing without rebound above baseline 6 weeks after a single dose. The nevirapine concentration was maintained above the target of 100ng/ml in infants at age 7 days, even in those infants not receiving a neonatal dose. This regimen has promise as prophylaxis against intrapartum and early breast milk transmission in a breastfeeding population.
Keywords: HIV vertical transmission, nevirapine, pharmacokinetics, Uganda